2014
DOI: 10.1016/j.diabres.2013.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of diabetes in HIV-infected adult patients: Evaluating the effect of diabetes mellitus on immune reconstitution

Abstract: SUMMARY We conducted a retrospective cohort study assessing the association between diabetes mellitus (DM) and immune recovery in HIV-infected adults. Immune reconstitution after initiating antiretroviral therapy was more rapid in DM patients (120.4 cells/year) compared to non-DM patients (94.2 cells/year, p < 0.023). Metformin use was associated with improved CD4 recovery (p= 0.034).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
(7 reference statements)
2
20
0
Order By: Relevance
“…We further propose that immunometabolism, which has been shown to affect the ability of T-cells to proliferate, would regulate optimal cytotoxic responses and influence the size of the HIV reservoir 23. Given metformin’s immunomodulatory properties,28–34 43 45 and its ability to improve CD4+ T-cell counts in one study of participants initiating ART,31 we propose that this antidiabetic medication may enhance T-cell effector function to control the HIV reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further propose that immunometabolism, which has been shown to affect the ability of T-cells to proliferate, would regulate optimal cytotoxic responses and influence the size of the HIV reservoir 23. Given metformin’s immunomodulatory properties,28–34 43 45 and its ability to improve CD4+ T-cell counts in one study of participants initiating ART,31 we propose that this antidiabetic medication may enhance T-cell effector function to control the HIV reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin promotes autophagy and modulates T-cell glycolysis by inhibiting mTOR, improving CD4+ T cell counts in diabetic PLWH initiating ART 31. The effects of metformin in PLWH may be due to: (1) its ability to overcome the inhibition AMPK by viral transactivator of transcription (Tat) protein32; (2) an anti-inflammatory effect on the intestine by suppressing nuclear factor κB activation33; (3) an indirect anti-inflammatory effect caused by the reduced production of cytokines such as tumour necrosis factor-alpha (TNF-α) and interleukin-1 (IL-1)34 and/or (4) changes in the composition of the gut microbiota which have been observed in mice and in humans 35–38.…”
Section: Introductionmentioning
confidence: 99%
“… 14 A small case–control study from Botswana suggested an association between efavirenz use and diabetes. 35 Randomized controlled trials showed significantly higher serum glucose concentrations in participants in the efavirenz arms than the following comparator antiretroviral drugs: nevirapine, 13 abacavir, 13 atazanavir, 11 atazanavir–ritonavir, 9 and raltegravir. 12 …”
Section: Discussionmentioning
confidence: 99%
“…To reduce systemic and local inflammation, pravastatin is already being used to treat HIV-infected patients (Toribio et al, 2017). Another possible treatment option is metformin, an antidiabetic, senolytic drug that might promote metabolic function in the AT, decrease inflammation, and modulate T cell activation (Moyo et al, 2014). Metformin's effects have been studied in HIV-infected people with diabetes, and the drug is currently being tested clinically in non-diabetic HIV-infected patients (Routy et al, 2019).…”
Section: Therapeutic Strategies Based On Metabolic Pathwaysmentioning
confidence: 99%